Overcoming digital divides in higher education: Digital literacy beyond Facebook. (November 2015) - Radovanović, Danica; Hogan, Bernie; Lalić, Danijela
The accelerated development of Information and Communications Technology has had a profound impact on the education system, both online and offline. In a South East European country such as Serbia, new technologies shape information, communication, and collaboration dynamics while contributing to a persistent digital divide regarding the skills necessary to obtain, process, evaluate, and communicate information. In this article, we explore digital divides between students and teachers in higher education with a focus on tensions surrounding digital literacy and collaboration. We apply Weber's theory of stratification to an empirical case study of the digital divide in higher education in Serbia. We draw upon international indicators, secondary statistical sources, and primary semi-structured interviews with students and teachers in higher education. Through this analysis, we illustrate how forms of stratification intervene when trying to integrate new technologies and technology-oriented practices into the classroom. We consider stratification in terms of the traditional digital divide of access as well as stratification along lines of status, politics, and motivations. We interpret educators' reluctance to adopt new technology as a reaction to the technology's capacity to challenge the educators' legitimacy, expertise, and preferred teaching materials. Students compound this situation with both greater familiarity and yet less focus on source credibility.